1989
DOI: 10.2307/1130790
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Understanding of Counting and Cardinality

Abstract: 4-year-old's knowledge of counting and cardinality--the last count word reached represents the numerosity of the set--was tested in 2 experiments. Experiment 1 investigated the nature of early cardinality responses by presenting different forms of the cardinality question before, after, and before and after the child counted. Both type and time of question has large effects. Experiment 2 examined whether children of this age could recognize errors in 4 counting procedures and whether they would reject a cardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 0 publications
6
96
1
6
Order By: Relevance
“…For example, three-year-old children violate the one-one principle by skipping or double-counting items, or by using the same numeral twice in a count (Baroody & Price, 1983;Briars & Siegler, 1984;Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Miller, Smith, Zhu, & Zhang, 1995;Schaeffer et al, 1974;Wagner & Walters, 1982). Children also frequently violate the stable-order principle by producing different number-word sequences at different times (Baroody & Price, 1983;Frye et al, 1989;Fuson et al, 1982;Fuson, Secada, & Hall, 1983;Miller et al, 1995;Wagner & Walters, 1982). These findings have led many observers to conclude that the how-to-count principles, rather than being understood intuitively, are in fact learned gradually.…”
Section: How Counting Represents 4 How Counting Represents Number: Whmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, three-year-old children violate the one-one principle by skipping or double-counting items, or by using the same numeral twice in a count (Baroody & Price, 1983;Briars & Siegler, 1984;Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Miller, Smith, Zhu, & Zhang, 1995;Schaeffer et al, 1974;Wagner & Walters, 1982). Children also frequently violate the stable-order principle by producing different number-word sequences at different times (Baroody & Price, 1983;Frye et al, 1989;Fuson et al, 1982;Fuson, Secada, & Hall, 1983;Miller et al, 1995;Wagner & Walters, 1982). These findings have led many observers to conclude that the how-to-count principles, rather than being understood intuitively, are in fact learned gradually.…”
Section: How Counting Represents 4 How Counting Represents Number: Whmentioning
confidence: 99%
“…After the child had counted the chips, the line was immediately covered with a piece of cardboard and the child was asked how many chips were Studies using a How-Many task have found that many children respond incorrectly to the "how many" question even after they have counted the array correctly. When asked "how many," children often try to count the set again, or (if prevented from recounting) either make no response or guess some numeral other than the last numeral in the count sequence (Frye et al, 1989;Fuson, 1992;Markman, 1979;Rittle-Johnson & Siegler, 1998;Schaeffer et al, 1974;Wynn, 1990;Wynn, 1992). Moreover, some investigators have concluded that the How-Many task overestimates children's knowledge, because some children actually do repeat the last numeral used in counting without (apparently) understanding that it refers to the cardinal value of the set-this superficial understanding has been called a 'Last-Word Rule' to distinguish it from the cardinal principle (Frye et al, 1989;Fuson, 1988).…”
Section: How Counting Represents 4 How Counting Represents Number: Whmentioning
confidence: 99%
See 2 more Smart Citations
“…It's in light of this evidence that we asserted that children's early counting is a routine that they learn without grasping its numerical significance. It is also the evidence that has led most researchers in the field to consider the debate between nativist and constructivist views of the acquisition of verbal counting to be settled in favor of the latter (Condry & Spelke, in press;Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Hurford, 1987;Le Corre et al, 2006;Schaeffer, Eggleston, & Scott, 1974;Siegler, 1991;Mix, Huttenlocher, & Levine, 2002;Wynn, 1992).…”
Section: Evidence That Knowledge Of the Counting Principles Is Constrmentioning
confidence: 99%